ChemInform Abstract: An Efficient Synthesis of 4H‐Chromene, 4H‐Pyran, and Oxepine Derivatives via One‐Pot Three‐Component Tandem Reactions. Issue 14 (20th March 2013) - Kazemi, Bagher; Javanshir, Shahrzad; Maleki, Ali; Safari, Mostafa; Khavasi, Hamid Reza
Abstract A tandem Michael addition — cyclization process of cyclic 1, 3‐diones with diesters such as (II) and malononitrile or ethyl cyanoacetate is developed to yield six‐ and seven‐membered O‐heterocycles.